Language in the relevant cultural space: the comparative analysis of conceptions of L. Wittgenstein and J. Derrida - Ganna Stoyatska (Cхід, 2016)
The executed study focuses its attention on the phenomenon of the language as the legitimation factor of cultural narratives and the space of metaphysics bases creation as the Western way of thinking grandnarrative. It scrutinizes the language role and status in the works by L. Wittgenstein and J. Derrida whose worldview systems differ greatly from the preceding metaphysic tradition and simultaneously preserve and inherit the classical principles of philosophizing. It has been proved that both philosophers have closeness of views in the matter of Western Philosophy genesis. The article emphasizes that L. Wittgenstein and J. Derrida have the same object of cognition, which is the postulate that there exist inviolable universals in a language structure: general rationalistic principles on the bases of which the whole system of Western Metaphysics is created. It has been demonstrated that within deconstructionism, as well as within L. Wittgenstein philosophy, different ways are used to confirm a language role as the specific instrument for expressing senses, which in the process of reality acquisition forwards semantic violence over it. The author considers that the main objective of the publication is to demonstrate the critical direction of the two conceptions concerning the language nature as the actual space for cultural narratives formation and the centerpiece for the creation of main metaphysical Western way of thinking senses. L. Wittgenstein and J. Derrida experience has great potential for understanding and solving contemporary humanitaristics key transformational problems. The article states that the tradition of own principles "revision", characteristic of the ХХ century philosophy, has different worldview grounds in different conceptions. But their common item is the recognition of the fact that these general universal principles are rooted, in the best part, in a language as a social way of thinking abstract model. In point of fact, in deconstructionism we deal not with basic ideas borrowings in a creative search of overcoming metaphysics, but with the so-called emanation of senses. At the advanced historical stage this phenomenon of emanation includes the actual experience of "overcoming" in the traditions set up by M. Heidegger, R. Karnap, L. Wittgenstein and acquires its utmost presentation in the works by J. Derrida.